Tragedy, comedy, power. On the artistic form of democracy - Villacañas Berlanga, José Luis (Estudios de Filosofía, 1995)
The central thesis held during this debate is rooted in Lessing and revolves around the final relation between the concepts of comedy, communication and democracy. The opposite pole is represented by the concepts of tragedy, solitary heroism and the aristocratic spirit whlch thus far have served as inspiration for Western politics. Comedy's strength lies in its demystification of power, thanks to its strategy of salvation of the present, of self- limitation and reciprocal recognition. The spur for this article was a reference made by Nietzsche to Plato and Macchiaveli.